Images du pouvoir royal dans les Travaux et les Jours d’Hésiode : une approche de Zeus dans le « mythe des races » - Karin Mackowiak (Kentron)
Did Hesiod elaborate a divine figure, Zeus, all devoted to the ideal of retributive justice? The so-called “myth of the five races / ages” needs to be put into a new perspective in order to make room for historian assumptions that consider the race of the heroes as a key to understand Zeus in this myth and to understand its relations with other passages recorded in the Works and Days. This study focuses on hesiodic poetic construction in concordance with the social and political background of VIIth century B.C. Greece.